Perceptual Underpinnings for "Good" Editing: A Fractal Analysis. (March 2020) - Blau, Julia J. C.; Carello, Claudia
Filmmakers' efforts not only advance film as an art form, they also provide insights about basic perception. This research was designed to uncover commonalities between the aesthetic appreciation of viewers of films and the perceptual capacities of observers of environmental events. We assessed whether the temporal structure of events in the environment is reflected in the temporal structure of events in film. Participants in Study 1 segmented neutral environmental events to establish a benchmark temporal structure. Study 2 compared the temporal structure of editing in amateur and professionally made films. Results from these two studies suggest a particular fractal structure common to environmental event perception and the editing structure of professional films. This hypothesis was then tested in an experiment that reedited one film so as to produce four different versions, each with a different fractal structure. These versions were evaluated by audiences in terms of aesthetics (e.g., general likability, comprehension, technical aspects of craft). The results suggest that the fractal structure typical of environmental event perception is preferred, even when it is not the original, artistically intended version. It is argued that narrative films succeed, at least in part, because their temporal structure reflects the temporal structure of environmental event perception.